Effectiveness of Intravitreal Dexamethasone Implant Treatment for Diabetic Macular Edema in Vitrectomized Eyes - Hüseyin Baran Özdemir; Murat Hasanreisoğlu; Murat Yüksel; Mestan Ertop; Gökhan Gürelik; Şengül Özdek (Türk Oftalmoloji Dergisi)

(untitled)
Objectives:To report the effectiveness and long-term outcomes of intravitreal dexamethasone implantation for diabetic macular edema (DME) in vitrectomized eyesMaterials and Methods:Medical records of patients were retrospectively reviewed. Time of pars plana vitrectomy (PPV), PPV indications, interval between DEX injection and PPV, other intravitreal treatment prior to DEX application, best corrected visual acuity (BCVA), intraocular pressure (IOP), and central retinal thickness (CRT) measured by optical coherence tomography were recorded.Results:Seventeen eyes of 17 patients were included in the study. The mean follow-up after DEX injection was 21±2.4 months (12-43 months). The female/male ratio was 11/6. Mean age was 60.7 years (46-70 years). Sixteen eyes (94.1%) were pseudophakic at the time of DEX treatment. The most common indication for PPV was tractional retinal detachment (8 eyes, 47.1%). Ten eyes (58.8%) received a single injection and a total of 30 DEX implantations were performed. Mean BCVA was 0.77 logarithm of the minimum angle of resolution (logMAR) units before the first injection and improved to 0.64, 0.68 and 0.66 logMAR after 1, 3 and 6 months, respectively (p<0.01). CRT decreased significantly from 452 µm at baseline to 310, 368±34 and 375 µm after 1, 3 and 6 months, respectively (p<0.04). Mean IOP was 16±1.2 mmHg at baseline and 18.2, 18.8 and 18.5 mmHg after 1, 3, and 6 months (p>0.05). Two eyes (%8) received topical anti-glaucoma medication (IOP≥25 mmHg). Similar results were observed in eyes receiving repeated DEX injections.Conclusion:Intravitreal DEX injection treatment seems to be effective for improving BCVA and decreasing CRT in vitrectomized eyes with DME. This effect seemed to last for 6 months in most eyes, but maximized at 3 months. Patients with repeated injections often require injection before 6 months.